Prenatal diagnosis of Wolf-Hirschhorn syndrome (4p-) in association with congenital diaphragmatic hernia, cystic hygroma and IUGR - (:unkn) unknown (My University, 2006)
Wolf-Hirschhorn syndrome (WHS) is a rare distinct clinical entity caused by a deletion of the short arm of chromosome 4. We report a case in which intrauterine growth restriction (IUGR), severe oligohydramnios, left-sided congenital diaphragmtic hernia (CDH), and cystic hygroma were detected by prenatal ultrasound examination at 27 weeks of gestation. A 29-year-old gravida 3, para 2, woman was referred at 26 weeks' gestation with suspicion of IUGR and cystic hygroma. Sonographic examination revealed IUGR with severe oligohydramnios, increased nuchal fold with cystic hygroma (left-sided diaphragmatic defect of Bochdalek type), and congenital diaphragmatic hernia. Chromosome analysis revealed a 46, XX, del(4)(p15.2) karyotype. Autopsy confirmed the ultrasound findings. Congenital diaphragmatic hernia (CDH) has rarely been described to be associated with WHS. CDH and cystic hygroma can lead to a diagnosis of this syndrome very early in life. We recommend genetic evaluation of a fetus with cystic hygroma, IUGR and CDH taking into consideration 4p deletion syndrome.
Keywords: Adult; Female; Humans; Pregnancy; Syndrome; Fetal Growth Retardation; Prenatal Diagnosis; Lymphangioma, Cystic; Craniofacial Abnormalities; Head and Neck Neoplasms; Chromosome Deletion; Chromosomes, Human, Pair 4; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital